Zur Bedeutung Eichendorffs in den Romanen von Horst Bienek - Orłowski, Hubert (Studia Germanica Posnaniensia, 2018)
In a cycle of novels of Horst Bienek (the so called Gliwice tetralogy: The first Polk Earth and fire, September light, Time without bells which cocreates the phenomenon of the new "Heimatliteratur" or the new "Grenzliteratur" (The literature of the border) we can find a distinct polemic with the understanding of the concept "Heimat" which (may be) was valid during Romanticism, when Eichendorff lived. Analysing four most important fragments of Gliwice tetralogy in which Horst Bienek - using varying narrations - gives subject and problems on the "presence" of von Eichendorff's works in the German community in Silesia of the 20's, 30's and 40's of our century; the author draws a conclusion that through the clash of experiences of the German Jew Montag with the evocated images of von Eichendorff of "Heimat", on the native land there occurs a kind of shattering of illusions of existence of the world - still possible during Eichendorff's times - based on "non-asymmetrical" categories (in Reinhard Kosellecks' understanding).